Differential analysis in infinite dimensional spaces : proceedings of an AMS special session held August 8-10, 1983, with partial support from the NSERC (Canada) - Sundaresan, Kondagunta; Speical Session on Differential Analysis in Infinite Dimensional Spaces; American Mathematical Society; Swaminathan, Srinivasa (Contemporary mathematics, 1986)
This volume focuses on developments made in the past two decades in the field of differential analysis in infinite dimensional spaces. New techniques such as ultraproducts and ultrapowers have illuminated the relationship between the geometric properties of Banach spaces and the existence of differentiable functions on the spaces. The wide range of topics covered also includes gauge theories, polar subsets, approximation theory, group analysis of partial differential equations, inequalities, and actions on infinite groups. Addressed to both the expert and the advanced graduate student, the book requires a basic knowledge of functional analysis and differential topology.